2008
DOI: 10.1149/1.2982571
|View full text |Cite
|
Sign up to set email alerts
|

Stain Etching with Ferric Ion to Produce Thick Porous Silicon Films

Abstract: Stain etching of silicon in aqueous solutions composed of FeCl3 + HF + concentrated (HCl, HClO4 or H2SO4) leads to brilliantly luminescent porous Si with a unique dual layer structure. The upper layer (~2 µm or more thick) exhibits bluer luminescence (peaked at 520-590 nm). The lower layer exhibits redder luminescence (peaked at 630-660 nm). The peak PL wavelength and the PL intensity both depend strongly on the excitation wavelength. Photoluminescence excitation (PLE) spectroscopy indicates that the upper and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Stain etching will never rival anodic etching for ultimate control over the characteristics of porous silicon (por-Si) films. However, recent formulations of stain etchants developed by Kolasinski and co-workers (1)(2)(3)(4) have greatly expanded the possibility of using stain etching as a reproducible and cost effective process for the production of thin films and powders (5) of por-Si. The enhanced reproducibility and simplicity of metal ion containing oxidants as opposed to nitrates and nitrites has also facilitated a more quantitative approach to investigating and understanding stain etching.…”
Section: Introductionmentioning
confidence: 99%
“…Stain etching will never rival anodic etching for ultimate control over the characteristics of porous silicon (por-Si) films. However, recent formulations of stain etchants developed by Kolasinski and co-workers (1)(2)(3)(4) have greatly expanded the possibility of using stain etching as a reproducible and cost effective process for the production of thin films and powders (5) of por-Si. The enhanced reproducibility and simplicity of metal ion containing oxidants as opposed to nitrates and nitrites has also facilitated a more quantitative approach to investigating and understanding stain etching.…”
Section: Introductionmentioning
confidence: 99%
“…To help us answer this question we need to measure s R,0 for at least one other species. We have already demonstrated that Ce(IV) effectively produces por-Si (7,16). We have also found that HIO 3 etches Si in HF(aq) but that por-Si formation is hampered by precipitation.…”
mentioning
confidence: 88%